Improving teaching quality in a public university : a case of UiTM / Rugayah Hashim … [et al.] - Hashim, Rugayah; Abdullah, Normah; Abd. Hamid, Hamidi; Musa, Mohd. Supi; Abdul Rahim, Rosli (Universiti Teknologi MARA, Shah Alam, 2006)
The Malaysian government is placing more emphasis on public universities to perform and contribute towards the economic growth through quality education (9MP, 2006). Hence to ensure this outcome, academic excellence at all the public universities are guided by five tenets or star areas which comprise of : teaching and learning, R&D, community services, internationalization and, harnessing the full potential of the university (MoHE, 2006). In Malaysia, the Ministry of Higher Education has divided public universities into two categories: teaching or research. Currently, UiTM is a teaching university as the university still offers diploma courses. However, UiTM aspires to be a research intensive university (RIU) by the year 2010.